Learning English Vocabulary Strategies for Non-English Department Students at Intensive English Class - Nurfauziah, Dwi Hana; Tenny Murtiningsih; Miftah Al Farhan (English Language Education, Universitas Internasional Batam, 2024)
This study aims to identify English vocabulary learning strategies used by non-English major students in the Intensive English Class (IEC) program, as well as explore the difficulties they face in the learning process. Using a qualitative case study approach, this research involved four students and four IEC tutors at a private university in Barito Kuala, South Kalimantan. Data were collected through classroom observations and in-depth interviews. The results of this study reveal that students use various strategies to learn vocabulary, namely recording new vocabulary along with its meaning and example sentences, memorizing by repeating, watching movies, or listening to English music, using online dictionaries or translator applications and asking directly to tutors or classmates. The strategy most often used by students is to record new vocabulary along with its meaning and example sentences, then the least used is asking directly to tutors or classmates. The main difficulties faced by students are lack of motivation and interest, as well as difficulties in understanding and applying vocabulary in various contexts, especially related to changes in word forms in sentences. The implication of the research is that students can increase their motivation in vocabulary acquisition through fun learning activities. Furthermore, teachers are also expected to be more creative, innovative, and give appreciation to students so as to create a pleasant learning atmosphere.